2018
DOI: 10.1186/s12889-018-6282-z
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death and predictors of childhood mortality in Rwanda: a matched case-control study using verbal social autopsy

Abstract: BackgroundRwanda has dramatically reduced child mortality, but the causes and sociodemographic drivers for mortality are poorly understood.MethodsWe conducted a matched case-control study of all children who died before 5 years of age in eastern Rwanda between 1st March 2013 and 28th February 2014 to identify causes and risk factors for death. We identified deaths at the facility level and via a community health worker reporting system. We used verbal social autopsy to interview caregivers of deceased children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…These findings are in agreement with previous studies that reported that the poorest households had a 29% greater risk of microscopic parasitaemia compared to the poorest houses (aRR 1.29; 95% CI 1.07-1.55) [39]. Additionally, lack of household electricity increased the childhood mortality in Rwanda, including malaria mortality (aOR: 1.4, 95% CI 1.0-1.8) [40]. The above is important because housing quality can affect malaria risk through its effect on house entry of the malaria vector [39].…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with previous studies that reported that the poorest households had a 29% greater risk of microscopic parasitaemia compared to the poorest houses (aRR 1.29; 95% CI 1.07-1.55) [39]. Additionally, lack of household electricity increased the childhood mortality in Rwanda, including malaria mortality (aOR: 1.4, 95% CI 1.0-1.8) [40]. The above is important because housing quality can affect malaria risk through its effect on house entry of the malaria vector [39].…”
Section: Discussionsupporting
confidence: 92%
“…Evidence suggests that maternal and neonatal mortality is associated with the complication that may arise any time during child birth without SBA [18][19][20][21]. In some of the developed countries, there is increasing trend of planned home delivery with evidence suggesting no difference in neonatal mortality and morbidity between planned home deliveries and hospital births [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Major drivers of persistently high childhood mortality are structural, including extreme poverty and lack of access to healthcare. In areas with declining childhood mortality, deaths often occur at home [ 5 ]. Barriers to accessing healthcare may therefore result in sub-populations with increased risk of childhood mortality, even in settings where overall mortality rates are declining.…”
Section: Introductionmentioning
confidence: 99%